PENANGGULANGAN RISIKO INVESTASI MELALUI STRUKTUR MODAL, TINGKAT SUKU BUNGA DAN NILAI TUKAR RUPIAH DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2018-2022) - Fatoni, Ramadhan Noor Rachman; Indarto, Indarto; Budiati, Yuli (JURNAL STIE SEMARANG, 2025)
Abstract This study has the following objectives to analyze the effect of capital structure, interest rates and rupiah exchange rates on profitability. To analyze the effect of capital structure, interest rates, rupiah exchange rate and profitability on investment risk. To analyze the effect of profitability in mediating between capital structure, interest rates and rupiah exchange rates on investment risk. The population amounted to 13 insurance companies listed on the Indonesia Stock Exchange with 34 processed data. The analytical tools used are 2-stage multiple linear regression analysis. The results of this study prove that capital structure has a significant negative effect on profitability. Interest rates and the rupiah exchange rate have no effect on profitability. Capital structure, interest rates and profitability have a significant negative effect on Investment Risk. The rupiah exchange rate does not affect the Investment Risk. Profitability can mediate the influence between the Capital Structure and the Rupiah exchange rate on Investment Risk. Profitability cannot mediate the effect between interest rates on Investment Risk.